Simultaneous Broadening and Enhancement of Cr3+ Photoluminescence in LiIn2SbO6 by Chemical Unit Cosubstitution: Night‐Vision and Near‐Infrared Spectroscopy Detection Applications. Issue 26 (19th May 2021) - Liu, Dongjie; Li, Guogang; Dang, Peipei; Zhang, Qianqian; Wei, Yi; Lian, Hongzhou; Shang, Mengmeng; Lin, Chun Che; Lin, Jun
Abstract: Near‐infrared (NIR)‐emitting phosphor materials have been extensively developed for optoelectronic and biomedical applications. Although Cr 3+ ‐activated phosphors have been widely reported, it is challenging to achieve ultra‐broad and tunable NIR emission. Here, a new ultra‐broadband NIR‐emitting LiIn2 SbO6 :Cr 3+ phosphor with emission peak at 965 nm and a full‐width at half maximum of 217 nm is reported. Controllable emission tuning from 965 to 892 nm is achieved by chemical unit cosubstitution of [Zn 2+ –Zn 2+ ] for [Li + –In 3+ ], which can be ascribed to the upshift of 4 T2g energy level due to the strengthened crystal field. Moreover, the emission is greatly enhanced, and the FWHM reaches 235 nm. The as‐prepared luminescent tunable NIR‐emitting phosphors have demonstrated the potential in night‐vision and NIR spectroscopy techniques. This work proves the feasibility of chemical unit cosubstitution strategy in emission tuning of Cr 3+ ‐doped phosphors, which can stimulate further studies on the emission‐tunable NIR‐emitting phosphor materials. Abstract : Controllable photoluminescence tuning of ultra‐broadband near‐infrared emitting LiIn2 SbO6 :Cr 3+ phosphor is achieved by chemical unit cosubstitution of [Zn 2+ –Zn 2+ ] for [Li + –In 3+ ], and its potential in night‐vision and NIR spectroscopic applications is demonstrated.